2010
DOI: 10.1088/0031-9155/55/15/008
|View full text |Cite
|
Sign up to set email alerts
|

GPU-based ultra-fast direct aperture optimization for online adaptive radiation therapy

Abstract: Online adaptive radiation therapy (ART) has great promise to significantly 10 reduce normal tissue toxicity and/or improve tumor control through real-time treatment adaptations based on the current patient anatomy. However, the major technical obstacle for clinical realization of online ART, namely the inability to achieve real-time efficiency in treatment re-planning, has yet to be solved. To overcome this challenge, this paper presents our work on the implementation of 15 an intensity modulated radiation the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
78
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 39 publications
0
78
0
1
Order By: Relevance
“…Adaptive radiotherapy (ART) has been proposed to ease this issue by imaging the patient's changed geometry during the treatment course and modifying the original, or reference, plan accordingly. [11][12][13][14][15][16][17][18][19][20] The new plan in either automatic treatment planning or ART replanning is supposed to inherit some clinically meaningful characteristics from the reference one. In this paper, we would like to consider dose-volume information in the form of the DVH as the common characteristic between the new and the reference plans.…”
Section: Introductionmentioning
confidence: 99%
“…Adaptive radiotherapy (ART) has been proposed to ease this issue by imaging the patient's changed geometry during the treatment course and modifying the original, or reference, plan accordingly. [11][12][13][14][15][16][17][18][19][20] The new plan in either automatic treatment planning or ART replanning is supposed to inherit some clinically meaningful characteristics from the reference one. In this paper, we would like to consider dose-volume information in the form of the DVH as the common characteristic between the new and the reference plans.…”
Section: Introductionmentioning
confidence: 99%
“…The GPU is a powerful, massively parallel programmable architecture, 7 which can be used to decrease the calculation time for many applications. In radiotherapy, the GPU has already been used in a wide range of applications (e.g., ray-tracing, dose calculation, and CT reconstruction techniques) [8][9][10][11][12][13][14] reporting speed-up ratios from 6 to 908.…”
Section: Introductionmentioning
confidence: 99%
“…based accelerations for re-planning are also possible using GPU-based optimization. A study by Men et al demonstrated how a graphics processing unit can reoptimize apertures taking only 0.7-2.5 s for prostate and head-and-neck plans 54. A commercially available knowledge based planning tool from Varian (RapidPlan) may also reduce planning times by relying upon an "atlas" of institutionally-approved plans to establish a baseline plan quality for an adapted plan-of-the-day.…”
mentioning
confidence: 99%